Pembangunan Aplikasi Kepegawaian untuk SD Islam Terpadu Yasir Di Cipondoh Tangerang - Djunaidi, Karina; Aziza, Rosida Nur; Haris, Abdul; P., Renaldi Bagas (TERANG, 2020)
SDIT Yasir is one of the schools under the management of the Ibnu Rusydi Islamic Education Foundation in Cipondoh, Tangerang. The school that aspires to create Indonesian young generations that resemble Ibnu Rusydi has several obstacles in carrying out daily teaching and learning activities. One of the issues is the teacher and staff data management. Therefore, the PKM team from the Informatics Engineering Department IT PLN intends to help the Yasir SDIT school by designing a web-based application for handling the employees. The application can be used to manage teacher and employee data, monitor teacher and employee attendances, and provide teacher performance assessments. Keywords: SDIT Yasir, PKM, Employee Information System